2017
DOI: 10.1093/ntr/ntx135
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Toxic Effect of Water-Pipe Smoking on the Early Stage of Embryonic Development

Abstract: This investigation addresses an important gap on the outcome of WPS during the early stage of embryogenesis. Data of this study point out that WPS can have a very toxic effect on the embryo at this stage. Additionally, results from this report display for the first time that WPS can damage normal angiogenesis of the embryo thus provoking a significant number of embryonic death. Moreover, this study reveals that this effect can occur via the deregulation of several genes related to cell apoptosis, proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 34 publications
4
17
0
Order By: Relevance
“…More specifically, we herein demonstrate that TP plant extract provokes an upregulation of ATF-3, BCL-2, INHB-A, and VEGF-C genes in heart and brain tissues. These data are consistent with our previous work vis-à-vis the outcome of waterpipe smoking (WPS) at the early stage of the normal development of the embryo [15], where we have demonstrated that these genes are important targets of the toxicity incited by WPS. Meanwhile, we report that TP plant extract induces an overexpression of CASPAS-8 in the heart and brain tissues in exposed embryos in comparison with their matched control.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…More specifically, we herein demonstrate that TP plant extract provokes an upregulation of ATF-3, BCL-2, INHB-A, and VEGF-C genes in heart and brain tissues. These data are consistent with our previous work vis-à-vis the outcome of waterpipe smoking (WPS) at the early stage of the normal development of the embryo [15], where we have demonstrated that these genes are important targets of the toxicity incited by WPS. Meanwhile, we report that TP plant extract induces an overexpression of CASPAS-8 in the heart and brain tissues in exposed embryos in comparison with their matched control.…”
Section: Discussionsupporting
confidence: 93%
“…While examining the embryos daily, we found that approximately 60%, 25%, and 10% of the embryos died 1, 2, and 3 days after the treatment, respectively, compared with the control groups in which <14% of the embryos died (Table 1). This effect on the control groups could be associated with manipulation, as reported in our previous studies [13,15,16]. Thus, TP extract decreases significantly the survival probability of the exposed embryos in comparison with their matched controls (Figure 1); meanwhile, it is important to highlight that 104 of 110 embryos died before 7 days (p < 0.001) of incubation.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations